Mathematical representation of joint angle measurement using step index optic fibre and linear array photodiode sensor - G. M., Salim; Mohd Anwar, Zawawi (IOP Publishing, 2020)
Human joint angle measurement involves various applications, for example monitoring of spine movement in sagittal and frontal planes, upper limb motion such as shoulder, neck and elbow, as well as lower limb motion such as hip, knee, and ankle. As the range of motions of different human joints are not similar, the output estimation of the designed sensor for these applications need to be carried out prior to sensor development. In this paper, the conceptual design of low-cost plastic optical fibre based on single step index fibre is illustrated, the mathematical modelling is explained, and the sensor’s hardware assemble is designed using CATIA software, before the estimated sensor output is presented. These results will be used as a reference values for actual optical fibre sensor design in the near future.